Australia 1:50 000 topographic survey. 4969-1, Hermit Creek - Australia. Army. Royal Australian Survey Corps (Canberra : Royal Australian Survey Corps, 1987)
Topographic map with relief shown by contours and spot heights. Some maps show mean temperature and average annual rainfall graphs.
Index to adjoining maps.
Keywords: Hermit Creek (N.T.) -- Maps; Topographic maps